Pengaruh Keterlekatan Karyawan dan Budaya Organisasi Terhadap Kinerja Karyawan: Studi Kasus Pada Start-Up Company - Octsa Khairus Praharsyarendra; Anggraini Sukmawati; Sukiswo Dirdjosuparto (Universitas Airlangga, 2020)
This study aims to determine the effect of employee engagement and organizational culture on the employee's performance. The data collection method uses the saturating sample that is by giving questionnaires to all employees. The number of respondents who filled out the questionnaire total of 30 people from all work units of the company, who are consisting of staff level to managerial level. The location of this research in PT Top karir Indonesia, Jakarta. The hypothesis testing is using Partial Least Squares (PLS). The results showed that organizational culture had a positive but insignificant effect on employee engagement, in contrast, employee engagement and organization culture has a positive influence on employee performance. The results of this study have implications for new companies or companies that are in the development stage in improving employee performance more effectively through employee engagement and organizational culture.